ANALISIS JALUR PENGARUH PRODUK DAN HARGA TERHADAP LOYALITAS KONSUMEN MELALUI KEPUTUSAN PEMBELIAN KOPI DI KABUPATEN JOMBANG: Studi Kasus : Coffee Shop Convo - Hidayati, Fifin Nur; Qomariyah, Siti Nur (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aims to determine the path analysis of the effect of product and price on consumer loyalty through coffee purchasing decisions at research locations, to determine the direct effect of product and price on purchasing decisions at Coffee Shop Convo. The method used in this study is a quantitative research method, and samples taken in this study were 96 respondents using the method of distributing questionnaires using Simple random sampling. The results of the study show that: (1) Products have a significant effect on purchasing decisions. (2) Price has a significant effect on purchasing decisions. (3) Products have a significant effect on consumer loyalty. (4) Price has no significant effect on consumer loyalty. (5) Purchase decisions have a significant effect on consumer loyalty. (6) Products do not affect consumer loyalty through purchasing decisions (7) Prices affect consumer loyalty through purchasing decisions